Small, Smaller, Nano: New Applications for Potato Virus X in Nanotechnology - Röder, Juliane; Dickmeis, Christina; Commandeur, Ulrich (Frontiers in Plant Science, 2019)
Nanotechnology is an expanding interdisciplinary field concerning the development and application of nanostructured materials derived from inorganic compounds or organic polymers and peptides. Among these latter materials, proteinaceous plant virus nanoparticles have emerged as a key platform for the introduction of tailored functionalities by genetic engineering and conjugation chemistry. Tobacco mosaic virus and Cowpea mosaic virus have already been developed for bioimaging, vaccination and electronics applications, but the flexible and filamentous Potato virus X (PVX) has received comparatively little attention. The filamentous structure of PVX particles allows them to carry large payloads, which are advantageous for applications such as biomedical imaging in which multi-functional scaffolds with a high aspect ratio are required. In this context, PVX achieves superior tumor homing and retention properties compared to spherical nanoparticles. Because PVX is a protein-based nanoparticle, its unique functional properties are combined with enhanced biocompatibility, making it much more suitable for biomedical applications than synthetic nanomaterials. Moreover, PVX nanoparticles have very low toxicity in vivo, and superior pharmacokinetic profiles. This review focuses on the production of PVX nanoparticles engineered using chemical and/or biological techniques, and describes current and future opportunities and challenges for the application of PVX nanoparticles in medicine, diagnostics, materials science and biocatalysis.